Distributed networked control system for power supply system of the accelerator based on CANopen protocol - Chepurnov, A.S.; Gribov, I.V.; Matveev, N.V.; Belogorskiy, K.A.; Nedeoglo, F.N. (Вопросы атомной науки и техники, 2006)
Network-based control system for a power supply unit of the linear accelerator was developed. Front-end level
of the system is based on CAN fieldbus with CANopen and CANEX application level protocols. Both local and remote
control for each CANopen node is provided. Level 2 control stations of the system are ARM9 CPU based machines,
operating under Linux OS. Разработана распределенная сетевая система управления для силового источника питания линейного ускорителя. Нижний уровень системы основан на технологии полевой шины CAN с прикладными протоколами CANopen и CANEX. Поддерживается локальный и удаленный доступ к каждому CANopen узлу. В компьютерах станций управления второго уровня используется процессор ARM9 с операционной системой Linux OS. Розроблено розподілену мережну систему керування для силового джерела живлення лінійного
прискорювача. Нижній рівень системи заснований на технології польової шини CAN із прикладними
протоколами CANopen і CANEX. Підтримується локальний і вилучений доступ до кожного CANopen вузлу.
У комп’ю-терах станцій керування другого рівня використається процесор ARM9 з операційною системою
Linux OS.